Monitoring systemic amyloidosis using MRI measurements of the extracellular volume fraction. (June 2013) - Campbell-Washburn, Adrienne E.; Price, Anthony N.; Ellmerich, Stephan; Simons, J. Paul; Al-Shawi, Raya; Kalber, Tammy L.; Ghatrora, Rupinder; Hawkins, Philip N.; Moon, James C.; Ordidge, Roger J.; Pepys, Mark B.; Lythgoe, Mark F.
Abstract We report the in vivo evaluation, in a murine model, of MRI measurements of the extracellular volume fraction (ECV) for the detection and monitoring of systemic amyloidosis. A new inducible transgenic model was used, with increased production of mouse serum amyloid A protein controlled by oral administration of doxycycline, that causes both the usual hepatic and splenic amyloidosis and also cardiac deposits. ECV was measured in vivo by equilibrium contrast MRI in the heart and liver of 11 amyloidotic and 10 control mice. There was no difference in the cardiac function between groups, but ECV was significantly increased in the heart, mean (standard deviation) 0.20 (0.05) versus 0.14 (0.04), p < 0.005, and liver, 0.27 (0.04) versus 0.15 (0.04), p < 0.0005, of amyloidotic animals and was strongly correlated with the histological amyloid score, myocardium, ρ = 0.67, p < 0.01; liver, ρ = 0.87, p < 0.01. In a further four mice that received human serum amyloid P component (SAP) followed by anti-human SAP antibody, a treatment to eliminate visceral amyloid deposits, ECV in the liver and spleen returned to baseline after therapy (p < 0.01). MRI measurement of ECV is a sensitive marker of amyloid deposits with potential application for early detection and monitoring therapies promoting their clearance.